2022
DOI: 10.1186/s13048-022-00969-3
|View full text |Cite
|
Sign up to set email alerts
|

A risk model of gene signatures for predicting platinum response and survival in ovarian cancer

Abstract: Background Ovarian cancer (OC) is the deadliest tumor in the female reproductive tract. And increased resistance to platinum-based chemotherapy represents the major obstacle in the treatment of OC currently. Robust and accurate gene expression models are crucial tools in distinguishing platinum therapy response and evaluating the prognosis of OC patients. Methods In this study, 230 samples from The Cancer Genome Atlas (TCGA) OV dataset were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…For example, SLC5A1, which was one of the 16 related up-regulated genes in CS group in our study, facilitates glucose transport (Mueckler and Thorens, 2013). A risk model found that SLC5A1 is one of the three hub genes that related to cisplatin therapy response in ovarian cancer (Chen et al, 2022). Several studies have also proved that an increased glycolysis rate can enhance the sensitivity to chemotherapy.…”
Section: Discussionsupporting
confidence: 57%
“…For example, SLC5A1, which was one of the 16 related up-regulated genes in CS group in our study, facilitates glucose transport (Mueckler and Thorens, 2013). A risk model found that SLC5A1 is one of the three hub genes that related to cisplatin therapy response in ovarian cancer (Chen et al, 2022). Several studies have also proved that an increased glycolysis rate can enhance the sensitivity to chemotherapy.…”
Section: Discussionsupporting
confidence: 57%
“…Previous approaches attempting to predict response to platinum-base d chemotherapy 28,29 and doxorubicin 30,31 have been developed based on gene expression signatures for specific tumour types. Gene expression-based classifiers are challenging to implement in the clinic as clinical samples are often a mix of tumour, immune and stromal cells with variable gene expression programs.…”
Section: Discussionmentioning
confidence: 99%
“…There are many different types of models based on clinicopathological parameters, imaging characteristics, or genetic signature to predict the stage, pathologic types, surgical outcomes, and reaction to chemotherapy, OS, or PFS, [42][43][44][45][46][47][48] but their practicability is limited partly owing to the expensive and redundant examination such as molecular diagnosis or genomic sequence. We urgently need models grounded on clinical variables with superior convenience.…”
Section: Dovepressmentioning
confidence: 99%